Effect of neighbourhood configurations on grain structure in CA models. (May 2014) - Zhou, J. X.; Wu, S. T.; Yin, Y. J.
Abstract : Cellular automata (CA) models for grain growth have been widely used, but the use of structured grid leads to anisotropy when nuclei cell begin to trap its neighbour cells, which may interfere with original preferential growth orientation. In this paper, CA neighbourhood configurations and trapping rules with strong anisotropy and stochastic preferential growth orientation were studied. A quantitative evaluation model was proposed to analyse the size, morphology and distribution of grain structure with an average diameter, shape factor, Feret diameter and Feret angle. The relationship between the fundamental CA model and grain structure was established. Characteristic parameters of different configurations were extracted, which helps the selection of different CA models.